2013
DOI: 10.1002/art.37852
|View full text |Cite
|
Sign up to set email alerts
|

Increased Male‐to‐Female Ratio Among Children Born to Women With Systemic Lupus Erythematosus: Comment on the Article by Lockshin et al

Abstract: New experimental evidence suggests that a subset of anti-DNA antibodies cross-reacting with the N-methyl-D-aspartate (NMDA) receptor can bind brainstem neuronal receptors, induce apoptosis, and result in a marked preferential loss of female fetuses in murine models of systemic lupus erythematosus (SLE) (1). Observational studies assessing the sex of offspring born to women with SLE are scant and limited by their sample size (2). In a recent study of 281 liveborn children of mothers with SLE, Lockshin et al did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
3
4
1
Order By: Relevance
“…In this large study, we did not confirm previous findings of male dominance among offspring born to women with SLE , which was predicted by mouse models . On the contrary, we observed a slightly lower proportion of male offspring born to women with RA or SLE compared with the general population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this large study, we did not confirm previous findings of male dominance among offspring born to women with SLE , which was predicted by mouse models . On the contrary, we observed a slightly lower proportion of male offspring born to women with RA or SLE compared with the general population.…”
Section: Discussioncontrasting
confidence: 99%
“…Reports of the sex ratio among offspring born to women with SLE are inconsistent and have generally not supported this finding. Several studies showed an increased male‐to‐female ratio , one showed no difference compared with the general population , and one study showed a higher proportion of female offspring .…”
mentioning
confidence: 99%
“…We also noted a trend toward an increase in female stillbirths in mothers with SLE compared to controls. This is consistent with our previous analysis of OSLER data showing a substantially greater male‐to‐female ratio among live offspring of mothers with SLE as compared to controls (OR 1.18 [95% CI 1.01, 1.38]) , although this has not yet been confirmed in a large population‐based study. Our findings are supported by recent experimental evidence suggesting that a subset of anti‐DNA antibodies cross‐reacting with the N ‐methyl‐ d ‐aspartate receptors can bind brainstem neuronal receptors and induce apoptosis, resulting in a marked preferential loss of female fetuses in murine models of SLE .…”
Section: Discussionsupporting
confidence: 90%
“…GluN2A is expressed earlier in female compared with male midbrain and mice lacking GluN2A exhibited no fetal loss in this model [116]. Interestingly, it was recently confirmed that mothers with SLE are more likely to have a male child [117]. This finding further supports the hypothesis that maternal antibodies may have gender-specific effects on brain development.…”
Section: Maternal Antibodies and The Fetal Brainsupporting
confidence: 55%